Rate-dependent crack nucleation in cartilage under microindentation. (August 2019) - Han, Guebum; Eriten, Melih; Henak, Corinne R.
Abstract: This study investigates rate-dependent crack nucleation in cartilage under microindentation using a poroviscoelastic framework and nano/microscopic images. Localized crack failure was induced at known locations and at different loading rates via microindentation with an axisymmetric sphero-conical indenter. Finite element (FE) modeling was used to reproduce results of microindentation tests within a poroviscoelastic framework. Scanning electron microscopy (SEM) was used to examine nano- and microscale structural features of crack surfaces. Microindentation results showed rate-dependent crack nucleation in cartilage. In particular, critical total work required for crack nucleation was larger at the slow loading rate compared to the fast loading rate. FE results suggested that viscoelastic relaxation of cartilage was a major contributor to the rate dependency and that tensile stresses localized at the indenter tip was a governing factor in crack nucleation. SEM images combined with microindentation and FE results suggested that the solid matrix in the vicinity of the tip experienced relatively large relaxation and kinematic fiber rearrangement at the slow loading rate in comparison to the fast loading rate. These findings extend current understanding of rate-dependent failure mechanisms in cartilage. Graphical abstract: Image 1 Highlights: Crack nucleation under microindentation was rate-dependent. Viscoelastic relaxation governed rate dependence in crack nucleation. Nano/microscopic features at crack surfaces were rate-dependent. Solid matrix relaxation and realignment delayed crack nucleation at slow rates.